Sociolinguistics and language teaching (Cambridge Univ. Press, 1996)
The book provides an introduction to the field of sociolinguistics for second and foreignlanguage teachers, as well as for teachers with students from linguistically diverse backgrounds. It covers the basic areas of sociolinguistics that have a bearing on language teaching, including regional and social linguistic variation, language and gender, World Englishes, and intercultural communication